Acute hypopituitarism - a rare complication of vasculotoxic snake bite: A case report - Amrish Saxena; Ajit Kumar Srivastava; Atul Singh Rajput; Iadarilang Tiewsoh; Ulhas N Jajoo (Wolters Kluwer Medknow Publications, 2014)
Venomous snake bite is an important public health hazard in tropical countries including India. Vasculotoxic snake bites are well known to cause local cellulitis, local tissue necrosis, bleeding manifestations, disseminated intravascular coagulation (DIC), acute kidney injury (AKI), shock, cardiac arrhythmia, neurotoxicity, coma, and death. We present the case of a 30-year-old female who was bitten by a Russell's viper snake and complicated by AKI, DIC, and acute hypopituitarism during her hospital course. Acute hypopituitarism as a complication of snake bite is a rare entity.